Sustainability Development Index of Reef Fisheries in Indonesia: A Case Study of Reef Fisheries at Ternate Island, North Maluku Province - Rumagia, Faizal; Boer, Mennofatria; Kurnia, Rahmat; Kamal, Mohammad Mukhlis (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2023)
Increasing of the fisheries problems, especially the decline of fisheries resources stock, made the sustainable issues become intense discussed in fisheries. The importance of the system indicator for fisheries sustainable development are widely known and have been done in several countries through tremendous effort in their fisheries development. In Indonesia, the assessment of fisheries sustainability has been carried out with various approaches to sustainability assessment, mostly on management status. This study aims to assess the rate of sustainable development and management of the reef fisheries in Indonesia using the integrated index approach of sustainability aspect using the multi-dimensional scaling procedures with a case study of reef fisheries at Ternate Island. The result shows that the sustainable development index of reef fisheries at the coastal area of Ternate Island tends to move toward sustainable development within integrated management from all sustainable dimensions. Dimensionally, economic and social dimensions show a positive trend on sustainable development, while ecological and technological dimensions tend to show the inverse direction. The relationship between economic and social benefits obtained from reef fisheries to improving the community well-being will provide a positive trend for the sustainability of reef fisheries. However, on the other hand, the increase in production can lead to overfishing for the reef fisheries resources. Management policy that integrated every indicator of sustainable fisheries dimension may extend the chance to develop reef fisheries at the coastal area of Ternate Island within the sustainability of the resources and ecosystems management.Keywords: Sustainable development, integrated management, fisheries management, sustainability index, coral reef